(untitled) (Research, Society and Development, 2022)
Objective: Apprehending the representations of puerperal women in the face of the experience of childbirth and the maintenance of the right to the companion in the midst of the Covid-19 pandemic. Methodology: A descriptive study with qualitative approach based on the reference of the Theory of Social Representations with methodological analysis of the Collective Subject Discourse. The study participants were 69 puerperal women, whose child was born during the Covid-19 pandemic, over 18 years old, with internet access. Data were collected between April and July 2020, through a semi-structured instrument made available via Google Forms®. Results and Discussion: Sixty-nine puerperals participated in this study, of an average age of twenty-seven years old. From the discourses emerged four central ideas: 1) Companion as a foundation; 2) Deprivation of the right to the companion; 3) Pandemic should not exclude the presence of the companion; 4) Misinformation about the pandemic. Conclusion: apprehending the representations of postpartum women in front of their experience in childbirth during the Covid-19 pandemic is necessary to reflect on the need to guarantee women’s rights, as well as to promote quality care for their health and their children.